Bovine immune response to African trypanosomes. Specific antibodies to variable surface glycoproteins of Trypanosoma brucei - Musoke, A.J.; Nantulya, V.M.; Barbet, A.F.; Kironde, F.; McGuire, T.C. (Wiley, 1981)
Cattle were infected with two different clones of Trypanosoma hrurei (MITat 1.2 and ILTat 1.3) and antibody response was followed by radioimmunoassay. In four of the seven animals there were at least two peaks of antibody activity to the infecting clones, with the second peak much higher than the first. Specific antibodies (IgG1 and IgM but not IgG2) were eluted from the immunoabsorbent columns on which the variant surface glycoproteins (VSGs) were coupled. By neutralization of infectivity tests, IgM antibodies from the first peak of antibody activity were more efficient in neutralizing trypanosomes than IgGl but the reverse was true of the antibodies isolated from the second peak. By absorption with multiple variable antigen types isolated during the course of infection, all the IgM and IgG1 in the first 3 weeks of infection were shown to be specific. It is suggested that polyclonal B cell stimulation leading to dysfunction in the control of IgM and IgG production may not be responsible for the high levels of these immunoglobulins in bovine trypanosomiasis.